THE RELATIONSHIP BETWEEN INDEPENDENT, DISCIPLINE AND LEARNING MOTIVATION WITH STUDENTS MATHEMATIC LEARNING OUTCOMES IN CLASS VII - Siti Nurjanah; Edi Prajitno (Universitas Ahmad Dahlan, 2018)
Low student learning outcomes are associated with several factors, including learning of independence, the discipline of learning, and motivation to learn. This research aims to determine whether or not a positive and significant relationship independent, discipline, and motivation to learn with the results of learning mathematics lessons for the student grade VII in Muhammadiyah Junior High School 2 Gamping (SMP Muhammadiyah 2 Gamping) Sleman district second semester in academic year 2016/2017. The population in this research comprises all of the students of grade VII SMP Muhammadiyah 2 Gamping Sleman district second semester in the academic year 2016/2017, consisting of 3 classes with a total of 108 students. The sample of this research is grade VIIC, 37 students, and the research experiment is grade VIIA which is 36 students and uses the random sampling technique to the class. The data collection technique is done by questionnaire and test method. Test of questionnaire instrument using a reliability test during the test of test instrument use validity test, a test of different power, and reliability test. Test prerequisite analysis is a test of normality, independent test, and linearity test. The data analysis for hypothesis testing using simple correlation analysis, multiple regression analysis, regression analysis of three variables. The results showed a positive and significant relationship between independent, discipline, and motivation to learn with the results of learning mathematics with = and , so obtained . The double correlation coefficient (R) is 0,5610 with regression equation relative contribution =23,624%, =64,488%, and 11,888% with the coefficient of determination (R2) is 0,3147 and effective contribution , =20,297%, and =3,742%.